The effect of low-dose esketamine on pain and post-partum depression after cesarean section: A prospective, randomized, double-blind clinical trial - Shen, Jiahong; Song, Congzhong; Lu, Xinlei; Wen, Yuxin; Song, Shaobo; Yu, Jing; Sun, Jianliang (Frontiers in Psychiatry, 2023)
Objective: To observe and evaluate the effect of a single intravenous injection of low-dose esketamine on postoperative pain and postpartum depression (PPD) in caesarean delivery patients. Methods: A total of 210 patients undergoing elective caesarean delivery were divided into an esketamine group (Group S, n=105) and a normal saline group (Group L, n=105) by a random number table. At 5 minutes after childbirth, patients in the S group were given 0.25 mg/kg esketamine, whereas patients in the L group received an equal volume of saline. The primary outcomes included postoperative pain control according to the Numerical Rating Scale (NRS) and the incidence of PPD according to the Edinburgh Postpartum Depression Scale (EPDS). The secondary outcomes included analgesia-related adverse events and Ramsay sedation scores. Results: The NRS pain (cough pain) score was lower in the S group than in the L group at 24 hours after surgery (P=0.016), and there was no significant difference in resting pain and mobilisation pain at 4h, 8h, and 48 h after surgery or resting pain at 24 h after surgery between the two groups. There was no significant difference in the prevalence of PPD between the two groups on the day before delivery, or at the first week, the second week or the fourth week after childbirth. At 5 minutes after dosing, the incidence of hallucinations (P<0.001) and dizziness (P<0.001) was higher in the S group than in the L group. At 15 minutes after dosing, the incidence of dizziness (P<0.001) and nausea (P=0.011) was higher in the S group than in the L group. The incidence of dizziness (P<0.001) was higher in the S group than in the L group when leaving the operating room. The Ramsay scores in Group S were lower than in Group L at 5 min (p<0.001), 15 min (p<0.001) after dosing and at the time of leaving the operating room (p<0.001). Conclusion: a single intravenous injection of 0.25 mg/kg esketamine did not reduce the incidence of depression at 1 w, 2 w or 4 w postpartum but improved pain during exercise at 24 h postoperatively.